Implementasi Sistem Informasi Akuntansi Pada Wijaya Service Menggunakan MYOB Accounting Plus V.18 ED - Cindya Windari; Adi Supriyatna; Mari Rahmawati (LPPM Universitas Bina Sarana Informatika, 2021)
Abstract - The development of information technology has developed very rapidly and rapidly, this can be seen from all aspects of life. One of the developments in information technology in the field of accounting is the presence of special accounting software or applications. Where this software serves to facilitate companies in making financial reports. Almost all companies are starting to switch from manual financial reporting systems to using a computerized system. However, in the era of increasingly advanced information technology, there are still some companies that still use manual systems both in data storage and in making financial reports. Wijaya service in managing its financial statements still uses a manual system, where for data storage and making financial reports still uses Microsoft Excel. So that the reports presented still often experience problems, such as incorrect calculations and takes a long time to make financial reports. MYOB Accounting Plus V.18 ED is one of the accounting software that is very easy to use and has interesting modules to use in the process of making financial reports. So it really helps Wijaya Service in processing financial reports that occur, because the calculation process and report generation are carried out automatically by the system, so that the data presented can be more accurate and more efficient. Keywords: Implementation, Accounting Information System, MYOB Application